Synthesis, structural and optical properties of ZnO-SiO₂ composite derived from waste coconut husk - Anuar, Muhammad Fahmi (2020)
The optical properties of ZnO-SiO2 composite had attracted a lot of attention this past decade. However, the production cost is quite high due to huge amount of high purity silica required in the synthesis process. Thus, alternative method was required especially using waste materials for example coconut husk. In this research, low cost ZnO-SiO2 composite were prepared by solid state reaction method using agricultural waste materials: coconut husk. The coconut husk was subjected to high temperature 500, 600, and 700 ºC to obtain coconut husk ash (CHA). CHA was then undergone chemical treatment (acid and alkali) as an attempt to increase its silica content. Thermogravimetry analysis (TGA) was carried out where it shows that most of the weight degradation of coconut husk during pyrolysis occurs at 221 ºC to 360 ºC. From X-ray fluorescence (XRF) analysis, the silica content increased from 8-11 % to more than 90 % for both acid and alkali treatment Moreover, the intensity of X-ray diffraction (XRD) peaks increased along the increased in temperature between 500 ºC to 700 ºC. The Field emission scanning electron microscopy (FESEM) images was analysed and showed rod-like structure of the CHA that was irregular in sizes and become slightly smaller after acid and alkali treatment. Besides that, broad bands were found by Fourier Transform Infrared spectroscopy (FTIR) at wavenumber 1066 cm⁻¹, 788 cm⁻¹ and 432 cm⁻¹ which related to Si-O-Si thus confirmed the presence of silica in CHA. The optical band gap of CHA untreated, acid treated, and alkali treated were 4.05 eV, 4.34 eV and 4.21 eV respectively. Next, ZnO-SiO2 composite were prepared by mixing zinc oxide (ZnO) powder with silica from CHA with 1:1 ratio by solid state method sintered at 600 ºC-1000 ºC to investigate the effect of sintering temperature on the properties of ZnO-SiO2 composite. First, XRD spectrum showed the zinc silicate was formed at sintering temperature 600oC and the peaks intensity increased along the sintering temperature. The composite shows well-distinct boundaries of rhombohedral-like particle when sintered at 1000 ºC that indicates the high crystallinity of the zinc silicate when sintered. Furthermore, the FTIR results shows the formation of Si-O-Si, ZnO4 and SiO4 vibration in the composite spectrum becoming narrow and stronger as the sintering temperature increased. The absorbance intensity of the ZnO-SiO2 composite was observed to decrease with the sintering temperature and the optical band gap of the composite at room temperature is 3.22 eV. The value increased to 3.26 eV at 600 ºC and decreasing until 900 ºC before rapidly increased to 4.05 eV at 1000 ºC. In the nutshell, the CHA has great potential to be used as silica substitute in preparation of ZnO-SiO2 composite.